The effect of a perpendicular and cumulative inlet flow on the mass-transfer distribution in parallel-plate electrochemical reactors - Colli, Alejandro Nicolás (2014)
A perpendicular inlet flow of electrolyte is analysed as a means of improving mass-transfer in a parallel-plate electrochemical reactor. Experimental local Sherwood numbers along the electrode length are reported for different values of the hydraulic diameter and Reynolds number, using the reduction of ferricyanide as a test reaction. The Reynolds numbers, evaluated with the inlet velocity in the reactor, range from 0.7 to 30 with interelectrode gaps varying between 3.2 to 9.8 mm. The perpendicular and cumulative flow makes uniform the mass-transfer distribution at the reactor inlet under laminar flow conditions. The experimental data are compared with theoretical calculations obtained by computational fluid dynamics and also with an analytical simplified model. The mean relative deviation between the experimental and theoretical results was lower than 5% and a close agreement was observed between both theoretical treatments.